Study of antibiotics resistance for Enterococcus faecalis isolated from different clinical casea in Al- Diwaniyah city - A. N.H. Al-musawi; H.S.M. Al-garawi (Al-Qadisiyah Journal of Pure Science, 2017)
Twenty tow hundred samples were collected from different clinical cases ofDiwaniyah Educational Hospital and Maternity and Children Hospital in the city ofDiwaniya , for the period from 20/11/2012 until 12/04/2013 . This study showed therewere 20 isolates of Enterococcus faecalis .This isolates distribted :10 isolates frominfections urinary tracts and 10 isolates from cases of diarrhea while not isolated frominfections of wounds and burns. Adopted qualities cultures and microscopic bacteriastudied, and tests biochemical , as diagnostic center Chrom agar and then the finaldiagnosis by a Vitek 2. conducted screening sensitivity to isolates studied direction(11), Susciptibity test was shown that isolates were resistant absolute directionantibiotics Erythromycin and Tetracycline and Rifampin and Ciprofloxacin and 100%, while showed these bacteria sensitivity of the absolute direction of anti Imipenemand by 100 % , and varied the direction of anti - resistance Chloramphenicol ,Nitrofurantoin and Penicillin Gentamycin and Vancomycin , with 50 % , 85% , 60 % ,70 % and 35 %, respectively. As the proportion of the total resistant to E.faecalisisolates the total antibiotic used in the study are higher than the sensitivity in terms ofresistance to more than 70% of these antibiotics.